Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7186/bgsm65201804
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology of the Shiranish Formation in the Mergasur area, Iraqi Kurdistan

Abstract: The Upper Cretaceous Shiranish Formation of Shkawtua Village, Mergasur area, Iraqi Kurdistan region consists of alternating mixed siliciclastic and carbonate strata interpreted as an outer shelf open marine (basinal) depositional environment. Fourteen thin sections were studied under polarized microscope to determine the petrographic component, fauna content, and microfacies analysis. The study tries to compare this formation with its equivalences throughout the region. Rock units are divided into: marly limes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…The present study is the first to document calciturbidite in the Zagros orogenic belt during the Late Cretaceous. All the previous literatures defined Shiranish Formation as of pelagite origin characterized by microfaunas and ammonites [1,2,9]. The present study has five significant outcomes; the first is the introduction of caliciturbidite facies which indicated transportation of carbonate sediments and deposition in deep basin by turbidity currents.…”
Section: Demirkan Section (Sharazoor Plain Section)mentioning
confidence: 66%
See 1 more Smart Citation
“…The present study is the first to document calciturbidite in the Zagros orogenic belt during the Late Cretaceous. All the previous literatures defined Shiranish Formation as of pelagite origin characterized by microfaunas and ammonites [1,2,9]. The present study has five significant outcomes; the first is the introduction of caliciturbidite facies which indicated transportation of carbonate sediments and deposition in deep basin by turbidity currents.…”
Section: Demirkan Section (Sharazoor Plain Section)mentioning
confidence: 66%
“…Similarly, an earlier work [8] defined the environment as a middle shelf to middle bathyal depositional one. Abdula et al [9] concluded a deep basinal, pelagic (open marine), frequently reducing euxinic environment of Shiranish Formation.…”
Section: Introductionmentioning
confidence: 99%
“…At Hijran section, the upper contact of the formation is conformable with the Aaliji Formation (Aba-Hussan, 1983), and also with Tanjero Formation in Sulaimani and Erbil areas and in the Shkawtua village near Mergasur town (Lawa, 2018: Abdula, 2018.…”
Section: Introductionmentioning
confidence: 84%
“…The Shiranish Formation in Shkawtua village of North Iraq consists of mixed siliciclastic and carbonate strata interpreted as an outer shelf open marine (basinal) depositional environment, and suggests an Upper Cretaceous age of the formation (Abdula et al, 2018). Al-Maamari & Al-Badrani (2019) studied the calcareous nannofossils of Shiranish Formation from well K-306 at northern Iraq and determined five biozones that refer to the upper Campanian Maastrichtian age.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latter age, the Bekhme Formation is separable from Aqra, Tanjero and Shiranish formations both spatially and temporally. The four formations cropped out in the Soran area (see Sissakian, 1997;Abdula et al, 2018b) and their separation is due to exposure in different stratigraphic positions. Thick succession of Tanjero and Shiranish formations (more than 500 m thick) separated the Aqra from Bekhme Formation in the Soran area where they have the age of Maastrichtian and Turonian-Middle Campanian as seen from Figure 13.…”
Section: Reasons For Assigning Turonian-middle Campanian Age For Bekh...mentioning
confidence: 99%